(3eHGOF GdhUhd Edi Yde GdCUhds - (3GdMdjs ((3bQjI TbQI s)
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdCRdjI hGdOhGe CeG HYO agPG cJGH eHGOF GdhUhd Edi Yde GdCUhd bO ETJed ef CUhd Gdabg Ydi eG dGHO efg s
(3BNQgG (B:s
(3HPdc Cf GdYde HPdc GdYOf GdCUdi agh Mb hEf CQGO hZjQg agh HGWd dCf GdYde hGdXf HGdfai dGHO dg ef Odjd hdjchf gPG BNQ eG JPcQg ai gPg GdebOeI hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg COYjg eHGQcIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs